Enhancing kidney function with thrombolytic therapy following donation after cardiac death: a multicenter quasi‐blinded prospective randomized trial. (30th October 2015) - Woodside, Kenneth J.; Goldfarb, David A.; Rabets, John C.; Sanchez, Edmund Q.; Lebovitz, Daniel J.; Schulak, James A.; Fung, John J.; Eghtesad, Bijan
Abstract: Kidneys from donors after cardiac death (DCD) are at risk for inferior outcomes, possibly due to microthrombi and additional warm ischemia. We describe an organ procurement organization‐wide trial utilizing thrombolytic tissue plasminogen activator (tPA) during machine pulsatile perfusion (MPP). A kidney from each recovered kidney pair was prospectively randomized to receive tPA (50 mg Alteplase) or no tPA (control) in the MPP perfusate. From 2011 to 2013, 24 kidneys were placed with enrolled recipients from 19 DCD kidney donors. There were no significant differences for absolute values of flow or resistance while undergoing MPP between the groups, nor rates of achieving discrete flow and resistance targets. While there was a trend toward lower creatinine and higher glomerular filtration rates in the tPA group at 3, 6, 9, and 12 months, these differences were not significant. Delayed graft function (DGF) rates were 41.7% in the tPA group vs. 58.4% in the control group (OR 0.51, 95%CI 0.10–2.59, p = 0.68). Death‐censored graft survival was similar between the groups. In this pilot study, encouraging trends are seen in kidney allograft function independent of MPP parameters following DCD kidney transplantation for those kidneys receiving thrombolytic tPA and MPP, compared with standard MPP.